1989
DOI: 10.1007/bf00140175
|View full text |Cite
|
Sign up to set email alerts
|

Severe summer ice in Hudson Strait and Hudson Bay following major volcanic eruptions, 1751 to 1889 A.D.

Abstract: Indices of summer sea ice severity in the eighteenth and nineteenth centuries have been reconstructed from sailing ships' log-books. The ice record for Hudson Strait extends from 1751 to 1889. Ice records are available for two parts of Hudson Bay and these extend from 1751 to 1870. The three records were derived from the same sources but the method of derivation applied in the bay was different to that applied in the strait. The years having the five largest ice indices in each of these records were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…The 1813-1826 estimated minimum temperatures from McCord also show colder winter temperatures compared to modern values, with the first peak shifted to between −5 to −3 ∘ C, but the shapes are similar for warmer and extreme temperatures (Figures 3(b) and 4(b)), which is reasonable given the 1810s are widely considered to have been one of the coldest decades of the past centuries, particularly in North America (Dupigny-Giroux, 2009;Chenoweth, 1996;Harrington, 1992;Catchpole and Hanuta, 1989;Wilson, 1982). …”
Section: Reconstruction Of Historical Minimum and Maximum Temperaturesmentioning
confidence: 60%
“…The 1813-1826 estimated minimum temperatures from McCord also show colder winter temperatures compared to modern values, with the first peak shifted to between −5 to −3 ∘ C, but the shapes are similar for warmer and extreme temperatures (Figures 3(b) and 4(b)), which is reasonable given the 1810s are widely considered to have been one of the coldest decades of the past centuries, particularly in North America (Dupigny-Giroux, 2009;Chenoweth, 1996;Harrington, 1992;Catchpole and Hanuta, 1989;Wilson, 1982). …”
Section: Reconstruction Of Historical Minimum and Maximum Temperaturesmentioning
confidence: 60%
“…This eruption released a large amount of particulate matter into the atmosphere, which resulted in significant climatic cooling over the Northern Hemisphere (McCormick et al, 1995). In Hudson Bay, the break-up of sea ice was delayed by about three weeks in the summer of 1992 (Environment Canada, 1992a, b), and a strong relationship between severe ice conditions in Hudson Bay and major volcanic eruptions has been documented (Catchpole and Hanuta, 1989). Stirling and Derocher (1993) noted that bears came ashore three weeks later in 1992 than in 1991 and speculated that polar bears remain on the sea ice, hunting seals, for as long as possible.…”
Section: Population Estimatementioning
confidence: 99%
“…An expanded sea ice state following volcanic eruptions is further supported by observations in Hudson Bay and Hudson Strait (the waters along the southern coast of Baffin Island). Ship records suggested that severe summer ice occurred in the years immediately following large volcanic eruptions during the 19th century [Catchpole et al, 1989]. Entombed vegetation collected from the margins of ice caps in north central Baffin Island and analyzed by Miller et al [2012] suggests two periods during the descent into the LIA with sudden advances in snow line.…”
Section: Introductionmentioning
confidence: 99%